Taṣnīf al-Istijabāt al-ʿĀṭifiyyah li al-Jamāʿah Tijāh al-Mawlid Simṭ al-Durar fī Majlis al-Hidāyah (Dirāsah Istiqbāliyyah Adabiyyah) - Miftahul Jannah; Syarifuddin Syarifuddin; Anshar Zulhemi; Zulkhairi Sofyan; Sarah Ahmad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
Abstract:When reading a literary work, readers naturally have their own opinions regarding the work. The presence of a literary work becomes valuable when it receives various forms of acceptance and responses from readers, which can be examined through several aspects, one of which is the readers’ emotional aspect. Therefore, this study aims to analyze the classification of readers’ emotional responses to Maulid Simth al-Durar using the approaches of Literary Reception and Literary Psychology. The researcher employed a descriptive qualitative analysis method by relying on data in the form of readers’ responses to this qasidah, focusing solely on the emotional aspect, with data collected through in-depth interviews, observations, and text analysis. The results of the study indicate, first, that readers give diverse emotional responses. This research contributes to understanding how readers respond to literary works and how literary works, in turn, influence readers.